Green Synthesis of Zinc Oxide Nanoparticles from Coriandrum sativum and Their Use as Fertilizer on Bengal Gram, Turkish Gram, and Green Gram Plant Growth - Varada V. Ukidave; Lalit T. Ingale (International Journal of Agronomy)
Plant growth and development rely on various factors, including mineral nutrients. Some are macronutrients like nitrogen, phosphorus, and potassium, whereas some are micronutrients like iron, magnesium, zinc, and a few vitamins. This experimental attempt was to check the stimulatory effect of zinc nanoparticles on pulse plant growth. The study was conducted on the green synthesis of zinc oxide nanoparticles using Coriandrum sativum leaves extract. The characterization of zinc oxide nanoparticles was studied using the X-ray diffraction (XRD), scanning electron microscope (SEM), and transmission electron microscope technique (TEM). The effect of zinc oxide nanoparticles as a fertilizer on pulses plant (Bengal gram, Turkish gram, and green grams) was studied in vitro. The seed germination rate, length of root and shoot, fresh weight, dry weight, and protein and chlorophyll content were measured in different media for assessment of zinc oxide nanoparticle’s growth stimulatory effects. The green synthesis of zinc oxide nanoparticles was confirmed with a size around 100 nm by transmission microscope technique. The germination rate of plants was 100% in MS media and MS media + nanoparticles. The present study found that the root length, shoot length, and weight were higher in MS media + nanoparticles followed by MS media, MS media only with nanoparticles, and MS media without zinc, respectively. It is found that the zinc oxide nanoparticles support seed germination and plant growth and also increase the protein and chlorophyll content. Significantly enhanced growth and development were evident in green gram and Turkish gram compared to that in Bengal gram in media treated with zinc oxide nanoparticles. The protein estimation results showed that the content was higher after 7 days in plants of Bengal gram (1.23 mg/ml), Turkish gram (1.19 mg/ml), and green gram (1.26 mg/ml) than that in roots and shoots. The application of MS media + ZnO nanoparticles results showed that chlorophyll content 12.6 mg/l was observed in other applications in the plant’s seedlings. In contrast, the absence of zinc decreases the germination rate, plant growth, chlorophyll, and protein content. This study confirms that the green synthesis of zinc oxide nanoparticles assessed from Coriandrum sativum leaves holds implication and should function as an active biofertilizer.